Air Traffic Safety Assurance Based on Flight Plan Risk Assessment and Early Warning - Ruiwei Liu; Siqi Hao; Yaping Zhang; Guan Lian (Journal of Advanced Transportation)
This article presents a novel risk assessment method for aircraft flight plans in a four-dimensional trajectory-based operation background. With the increasing air transport volume and airspace demand and during the allocation and modification of flight plans, safety should also be considered in addition to economic benefits and competitiveness. By employing the time geography concept, this article first quantifies the space-time accessibility and estimates the visiting probability of aircraft in the four-dimensional trajectory-based operation context. On this basis, this article studies the method and process to evaluate the conflict risk between one flight plan and a special airspace, the weather-influenced airspace, and another flight plan. This article also proposes the conflict risk alerting strategy. The achievements of the study are expected to provide assistance for air traffic controllers in strategic conflict avoidance and are of great significance in assuring air transport safety.